Applying color theory to digital media and visualization - Rhyne, Theresa Marie (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2013)
"This book provides an overview of the application of color theory concepts to digital media and visualization. It highlights specific color concepts such as color harmony and shows how to apply the concept with case study examples and usage of actual online and mobile color tools. Color deficiencies are reviewed and color tools for examining how a specific color map design will look to someone with the deficiency are discussed. ... This book applies fundamental color concepts to digital media and visualization solutions. It is intended for digital media and visualization content creators and developers."--Back cover.
Introduction to color models -- Review of color vision principles -- Defining color gamut, color spaces, and color systems -- Defining color harmony -- Analyzing and modifying with online and mobile color tools -- Case study examples of colorizing visualizations -- Review of basic concepts covered.
Includes bibliographical references and index.
Keywords: Color -- Data processing; Color in design; Color computer graphics; Color vision; Information visualization; COMPUTERS -- Computer Graphics; Color computer graphics; Color -- Data processing; Color in design; Color vision; Information visualization